TANGGUNG JAWAB PEMDA TERHADAP KERUSAKAN LINGKUNGAN HIDUP KAITANNYA DENGAN KEWENANGAN PERIZINAN DI BIDANG KEHUTANAN DAN PERTAMBANGAN - Marhaeni Ria Siombo (Faculty of Law, Universitas Jenderal Soedirman, 2014)
Indonesia government has been struggling for implementing the concept of sustainable development nationwide. The Act No. 32 of 2004 on Regional Government gives the authority to local government widely, particularly relate to license of natural resources exploration in forestry and mining. Local Government has a strategic role with the given authority to issue IUP Exploration and IUP Production Operation, for mining businesses. Mining activities are very susceptible to environmental damage. Therefore, the authority given to local governments should be implemented with full responsibility. Moreover, they should realize that their role as local governments is essential in maintaining environmental quality in the region. At this point, in many cases, many local government officials have chances to violate their authority. Consequently, corruption is not inevitable. Ultimately environmental considerations are not a priority or primary consideration. The environmental damage that occurred in the region is the responsibility of local government, as part of the given authority.Key words : environmental damage, the mining licensing authority (IUP), the responsibility of local governments.